2013
DOI: 10.1111/scs.12105
|View full text |Cite
|
Sign up to set email alerts
|

Visible and invisible caring in nursing from the perspectives of patients and nurses in the gerontological context

Abstract: Our data revealed more nuanced insight into the meaning of invisible and visible caring in nursing within the gerontological context than has been previously reported in the literature. This has implications for nursing education and practice because it may help nurses meet the actual needs of older patients in hospital settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 31 publications
1
28
0
2
Order By: Relevance
“…This, to a large extent, refers to invisible tasks essential for health service delivery [22]. An Italian study demonstrated that nurses described invisible care as reflexivity, review of care actions, collaborating with colleagues, being 'competent', and being aware of their clinical skills [23]. These phenomena were also mentioned by the participants when reflecting nursing activities being visible through the RAFAELA system.…”
Section: Discussionmentioning
confidence: 99%
“…This, to a large extent, refers to invisible tasks essential for health service delivery [22]. An Italian study demonstrated that nurses described invisible care as reflexivity, review of care actions, collaborating with colleagues, being 'competent', and being aware of their clinical skills [23]. These phenomena were also mentioned by the participants when reflecting nursing activities being visible through the RAFAELA system.…”
Section: Discussionmentioning
confidence: 99%
“…In one longitudinal QD study (Kneck, Fagerberg, Eriksson, & Lundman, 2014), the researchers presented the findings as key patterns of learning for persons living with diabetes; in another longitudinal QD study (Stegenga & Macpherson, 2014), findings were presented as processes and themes regarding patients' identity work across the cancer trajectory. In another two studies, the researchers described and compared themes or categories from two different perspectives, such as those of patients and nurses (Canzan, Heilemann, Saiani, Mortari, & Ambrosi, 2014) or of parents and children (Marcinowicz et al, 2014). Additionally, Ma (2014) reported themes using both participants' language and the researcher's language.…”
Section: Presentation Of Findingsmentioning
confidence: 99%
“…The concept of care is central to the development of nursing practice, but has been (and remains) a slippery concept that is difficult to nail down. [54][55][56][57] In line with the dual processing perspective of expert clinical practice, [58] caring needs to be viewed simultaneously as the interaction between "interpersonal interaction" and "therapeutic intervention", [51] so that it may add coherence to the complex experiences of being a patient and being a carer. The central position of "care" (as indicated in Figure 3) is exactly where one might anticipate finding a threshold concept to allow it to perform its integrative function.…”
Section: Resultsmentioning
confidence: 99%